Six Commandments of Treatment Protocols During Covid-19 Pandemic in Dentistry - Agung Sosiawan; Dian Agustin Wahjuningrum; Anuj Bhardwaj; Kratika Mishra; Sheetal Khandelwal; Amit Bhardwaj; Shivani Bhardwaj (Biomolecular and Health Science Journal, 2021)
In December 2019, an outbreak in the city of Wuhan, Hubei China occurred and was named COVID- 19 by the World Health Organization and declared as a pandemic on January 30, 2020. The etiologic agent of acute respiratory disease is the novel corona virus 2019 (2019-nCoV) or the extreme acute respiratory syndrome corona virus 2 (SARS-CoV-2). During many dental operations, aerosols are produced and these aerosol methods, which are major problems for dentists, have become the main area of concern in dentistry. Dentists are at greatest risk since they are located close to the oropharynx. This study summarizes the effect of coronavirus disease 2019 (COVID-19) on dental care, administration, and emergency dental treatment service. It also identifies COVID-19 and explains about six commandments for dental practitioners during the treatment process to be practiced during the pandemic.